Hands-on machine learning for cybersecurity safeguard your system by making your machines intelligent using the Python ecosystem - Halder, Soma; Ozdemir, Sinan (Packt Publishing, 2018)
The book will allow readers to implement smart solutions to their existing cybersecurity products and effectively build intelligent solutions which cater to the needs of the future. By the end of this book, you will be able to build, apply, and evaluate machine learning algorithms to identify various cybersecurity potential threats.